Contracts and capabilities: public service interpreting and third sector domestic violence services. (3rd April 2017) - Tipton, Rebecca
ABSTRACT: This article evaluates the role played by professional and non-professional volunteer interpreters in the care trajectories and institutional itineraries of survivors of domestic abuse in the third sector and is informed by Martha C. Nussbaum's capabilities approach to contractarian theory. Reporting on a case study involving an organisation in the North West of England, it sheds light on how interpreter provision supports survivors in converting capabilities into effective social participation, and the extent to which survivors are able to influence the initial contract position in relation to language services provision. It finds that rather than being used as a replacement for professional interpreting, nonprofessional volunteer interpreters support survivors in ways that help them to achieve a range of service outcomes. Further, it finds that the evolving contractual relation places demands on professional interpreters to limit their role in interaction as the service user prepares to move on independently. I conclude that the capabilities approach provides a useful theoretical lens for examining service user empowerment in multilingual service spaces, especially in light of recently observed failings in rights-based approaches to interpreting and translation provision. The approach widens the debate about what constitutes socially responsible language services provision in this setting.